Pengaruh Kompensasi, Lingkungan Kerja, Dan Kompetensi Karyawan Terhadap Kinerja Karyawan Ud. Berkah Andita Mandiri Group Kab. Kediri - Rizka Fitriana; Moch. Saleh Udin; Taufik Akbar (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
This research was conducted with the aim of explaining the influence of compensation, work environment and employee competency on employee performance at UD. Berkah Andita Mandiri Group. The variables in this research are Compensation (X1), Work Environment (X2), Employee Competency (X3) and Employee Performance (Y). This research uses data collection techniques in the form of observation, interviews, and distributing questionnaires to UD employees. Blessings Andita Mandiri Group. This research has a population of 84 respondents and a sample of 70 respondents. The techniques for normality testing, heteroscedasticity testing, linearity testing, multicollinearity testing and hypothesis testing are expected to be able to answer the four problem formulations in this research. The analysis was carried out using SPSS for Windows version 25 software. Based on the results of the tests carried out, it can be concluded that: Compensation (X1) partially has a significant effect on employee performance (Y) at UD. Blessings Andita Mandiri Group. Work Environment (X2) partially has a significant effect on employee performance (Y) at UD. Blessings Andita Mandiri Group. Competency (X1) partially has a significant effect on Employee Performance (Y) at UD. Berkah Andita Mandiri Group; Compensation, work environment and competency simultaneously have a significant effect on employee performance and Competency simultaneously have a significant effect on Employee Performance (Y) at UD Berkah Andita Mandiri Group.